Выбор оружия: [фантастический роман] / Андрей Левицкий - Левицкий Андрей Юрьевич (S.T.A.L.K.E.R, 2008)
Экземпляры: РБ (20170306) / Инвентарный номер: 45352 / Цена: 247.00 / Авт.знак: Л 37 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6